2004
DOI: 10.1002/ceat.200401988
|View full text |Cite
|
Sign up to set email alerts
|

CFD Modeling of Turbulent Jacket Heat Transfer in a Rushton Turbine Stirred Vessel

Abstract: CFD modelling of the turbulent heat transfer was performed for a stirred tank equipped with a Rushton turbine impeller and four standard baffles. Eight different turbulence models, i.e. the standard k-e, RNG k-e, realizable k-e, Chen-Kim k-e, optimized Chen-Kim k-e, standard k-x, k-x SST and Reynolds stress models, were used during the modelling. In all investigated cases, the boundary flow at the vessel wall was described by the standard logarithmic wall functions. The CFD modelling values of the local heat t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 7 publications
1
15
0
1
Order By: Relevance
“…Distributions of the heat transfer coefficient on the side of the fluid in a jacketed, baffled agitated vessel strongly depend on the impeller type. This statement confirms the results of local heat transfer obtained for different single impellers, (for example, centrally located Rushton turbine 12,18,19,29 , six-bladed PBT 30,31 , Pfaudler 32,33 , HE 3 23,24 , CD 6 26,27 , four-bladed pitched paddle 19 or MR210 impeller 19 and off-centred propeller 20,33 , HE 3 20,34 , A 315 17 or Rushton turbine 17 ) as well as for two impellers on a common shaft 22,[35][36][37] .…”
Section: Introductionsupporting
confidence: 88%
“…Distributions of the heat transfer coefficient on the side of the fluid in a jacketed, baffled agitated vessel strongly depend on the impeller type. This statement confirms the results of local heat transfer obtained for different single impellers, (for example, centrally located Rushton turbine 12,18,19,29 , six-bladed PBT 30,31 , Pfaudler 32,33 , HE 3 23,24 , CD 6 26,27 , four-bladed pitched paddle 19 or MR210 impeller 19 and off-centred propeller 20,33 , HE 3 20,34 , A 315 17 or Rushton turbine 17 ) as well as for two impellers on a common shaft 22,[35][36][37] .…”
Section: Introductionsupporting
confidence: 88%
“…The working fluid was water and the temperature at the surface of the tank wall was set to 371.15 K. The testing data are provided in Table . It should be highlighted that no independence test was required for the number of mesh elements because the coarser mesh was already sufficiently refined (2 950 000 elements) for a mixing tank, as compared to the values found in the literature . The data of the mesh level 4 proved to be enough and an average value of 0.1 for the y + variable was used, which is the same value obtained by Jaimes and Nunhez .…”
Section: Model Formulationmentioning
confidence: 76%
“…The boundary conditions and additional considerations were adopted based on the results of previous research that found the most accurate models to describe the physical phenomenon in stirred tanks and with heat transfer . Some of these considerations are the following: A non‐slip boundary condition was applied on the solid walls (cylindrical wall, bottom, baffles, impeller, and shaft), so the fluid velocity at the wall is zero due to the viscous effects. The surfaces of the shaft in both rotating and stationary domains were considered rotating walls that have the same rotational speed as the impeller. In the free surface of the fluid domain, the free slip condition was used considering that the free surface is flat (no central vortex). The thermal boundary condition was defined as a fixed heating temperature Tw = 371.15 K. This value is taken as the average temperature reached by the wall in the experimental study of Strek with the steam supplied in the jacket. …”
Section: Model Formulationmentioning
confidence: 99%
“…GAMBIT 2.2.30 and FLUENT 6.2.16 were used for creation of geometries and meshes, and analysis of airflow, respectively. The viscous model used for the simulation was selected according to k-ε standard which has been previously applied for various areas (Lee and Short, 2001;Bhattacharya et al, 2002;Yang et al, 2003;Zakrzewska et al, 2004). Conditions and meshes generated for the CFD simulation are listed in Table 1.…”
Section: Design and Simulation Of The Fan-aspirated Radiation Shieldmentioning
confidence: 99%